Professional ASP.NET MVC 5 - Galloway, Jon; Wilson, Brad; Allen, K. Scott; Matson, David (Wrox professional guides, 2014)
ASP.NET MVC insiders cover the latest updates to the technology in this popular Wrox reference MVC 5 is the newest update to the popular Microsoft technology that enables you to build dynamic, data-driven websites. Like previous versions, this guide shows you step-by-step techniques on using MVC to best advantage, with plenty of practical tutorials to illustrate the concepts. It covers controllers, views, and models; forms and HTML helpers; data annotation and validation; membership, authorization, and security. -MVC 5, the latest version of MVC, adds sophisticated features such as single page applications, mobile optimization, and adaptive rendering -A team of top Microsoft MVP experts, along with visionaries in the field, provide practical advice on basic and advanced MVC topics -Covers controllers, views, models, forms, data annotations, authorization and security, Ajax, routing, ASP.NET web API, dependency injection, unit testing, real-world application, and much more Professional ASP.NET MVC 5 is the comprehensive resource you need to make the best use of the updated Model-View-Controller technology.